Pitotube: Inovasi Media Pembelajaran Youtube dalam Menulis Teks Pidato Siswa Kelas VIII SMPN 1 Galis Pamekasan - Gita Ananda Putri; Moh. Hafid Effendy; Mochamad Arifin Alatas (Universitas Sebelas Maret, 2025)
This study was conducted with the aim of evaluating the effectiveness of the innovation of utilizing YouTube media as a learning tool to improve the skills of writing speech texts for class VII students of SMPN 1 Galis Pamekasan. This research method uses a qualitative approach with observation techniques to observe the learning process that integrates YouTube videos as the main media. The results of the study show that YouTube as a learning medium has a good impact on students' understanding of the structure and content of speech texts. This media is able to foster students' interest in learning and student activity during the learning process. In addition, the speech videos that are shown provide real examples that make it easier for students to compose speech texts systematically and creatively. The obstacles found include limited supporting facilities such as internet connections and multimedia devices, as well as differences in writing abilities between students who still need more intensive guidance from teachers. Overall, learning innovations using YouTube can be an effective alternative in the process of learning Indonesian, especially related to speech texts, with the note that there is adequate infrastructure support and teacher assistance. This study suggests that teachers continue to develop digital media-based learning strategies to improve the quality of learning in the current technological era.Penelitian ini dilakukan dengan tujuan mengevaluasi sejauh mana efektivitas inovasi pemanfaatan media YouTube sebagai sarana pembelajaran untuk meningkatkan keterampilan menulis teks pidato pada siswa kelas VII SMPN 1 Galis Pamekasan. Metode Penelitian ini menggunakan pendekatan kualitatif dengan teknik observasi untuk mengamati proses pembelajaran yang mengintegrasikan video YouTube sebagai media utama. Hasil penelitian menunjukkan bahwa YouTube sebagai media pembelajaran berdampak baik pada pemahamansiswa mengenai struktur dan isi teks pidato. Media ini mampu menumbuhkan minat siswa untuk belajar serta keaktifan siswa selama proses pembelajaran berlangsung. Selain itu, video pidato yang ditayangkan memberikan contoh nyata yang memudahkan siswa dalam menyusun teks pidato secara sistematis dan kreatif. Kendala yang ditemukan meliputi keterbatasan fasilitas pendukung seperti koneksi internet dan perangkat multimedia, serta perbedaan kemampuan menulis antar siswa yang masih memerlukan bimbingan lebih intensif dari guru.Secara keseluruhan, inovasi pembelajaran menggunakan YouTube dapat dijadikan alternatif efektif dalam proses belajar Bahasa Indonesia, khususnya terkait teks pidato, dengan catatan adanya dukungan infrastruktur dan pendampingan guru yang memadai. Penelitian ini mengusulkan agar guru terus mengembangkan strategi pembelajaran berbasis media digital untuk meningkatkan kualitas pembelajaran di era teknologi saat ini.